2013
DOI: 10.1089/scd.2013.0403
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Novel Collaborative Structures for the Identification and Resolution of Barriers to Pluripotent Stem Cell Translation

Abstract: Increased global connectivity has catalyzed technological development in almost all industries, in part through the facilitation of novel collaborative structures. Notably, open innovation and crowd-sourcing-of expertise and/ or funding-has tremendous potential to increase the effi ciency with which biomedical ecosystems interact to deliver safe, effi cacious and affordable therapies to patients. Consequently, such practices offer tremendous potential in advancing development of cellular therapies.In this vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…20,21 The CTSCC was formed to unify international and multidisciplinary luminaries from major stakeholder groups to break down translational barriers. 1,22 Through disseminating timely and clear findings reflecting contemporary opinions of sector leaders, the aim of this effort will make a practicable contribution to stem cell translation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 The CTSCC was formed to unify international and multidisciplinary luminaries from major stakeholder groups to break down translational barriers. 1,22 Through disseminating timely and clear findings reflecting contemporary opinions of sector leaders, the aim of this effort will make a practicable contribution to stem cell translation.…”
Section: Resultsmentioning
confidence: 99%
“…1,23 And in so doing, de-risking and maximizing the overall research and development product of the field ultimately benefits patients suffering with debilitating diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the potential of bringing exogenous iPSC progeny to the clinic, scaling up with batch‐to‐batch consistency becomes a primary concern (Brindley et al , ). For that reason, synthetic peptide‐functionalized substrates may be challenging owing to their high manufacturing costs and extra conjugation steps (Place et al , ).…”
Section: Engineered Biomaterials For the Expansion Of Ipscsmentioning
confidence: 99%
“…Although access to materials and data has been identified as especially critical to stem cell science [ 13 ] it has been suggested that the stem cell community has been somewhat slower to respond to the changing frameworks of biomedical innovation and translation. [ 4 ] Unlike genomic and other medical data, which can readily be digitised and shared through Information Communication Technology (ICT) platforms, stem cell research (SCR) involves material biological objects, which can only be shared through physical transportation between locations and partners. SCR therefore at least potentially raises different and unique challenges for sharing material and data amongst large academic industry research consortia.…”
Section: Introductionmentioning
confidence: 99%